Fluorescent Molecular Rotors for Viscosity Sensors - Lee, Seung Chul; Heo, Jeongyun; Woo, Hee Chul; Lee, Ji Ah; Seo, Young Hun; Lee, Chang Lyoul; Kim, Sehoon; Kwon, O. Pil (Chemistry - A European Journal, 2018)
Fluorescent molecular rotors (FMRs) can act as viscosity sensors in various media including subcellular organelles and microfluidic channels. In FMRs, the rotation of rotators connected to a fluorescent π-conjugated bridge is suppressed by increasing environmental viscosity, resulting in increasing fluorescence (FL) intensity. In this minireview, we describe recently developed FMRs including push–pull type π-conjugated chromophores, meso-phenyl (borondipyrromethene) (BODIPY) derivatives, dioxaborine derivatives, cyanine derivatives, and porphyrin derivatives whose FL mechanism is viscosity-responsive. In addition, FMR design strategies for addressing various issues (e.g., obtaining high FL contrast, internal FL references, and FL intensity-contrast trade-off) and their biological and microfluidic applications are also discussed.
Keywords: Fluorescence dynamics; Micro fluidic applications; Microfluidic channel; Microviscosities; Molecular rotors; Porphyrin derivatives; Subcellular organelles; Viscosity sensor; fluorescence dynamics; fluorescent molecular rotors; microviscosity; molecular rotors; viscosity sensors